Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1055/s-0030-1249574
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Temporalis Muscle Atrophy and the Use of Electrocautery: A Volumetric MRI Comparison

Abstract: Postoperative temporalis muscle atrophy from injury to the neurovascular supply can cause significant cosmetic disfigurement, and avoidance of electrocautery use has become a common practice in minimizing this outcome. We attempted to quantify the effects of electrocautery on temporalis atrophy by retrospectively reviewing postoperative magnetic resonance images in patients having undergone an orbital frontal craniotomy. We reviewed medical records and compared volumetric measurements of the temporalis muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…1,2,3,6,11,12,15,19,23,24,29 Oikawa et al published the most often referenced modification. 21 They reported cosmetically satisfactory outcomes in 100 patients, which were obtained by avoiding the use of electrocautery and dissecting the temporal muscle in a retrograde fashion.…”
Section: Aesthetic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3,6,11,12,15,19,23,24,29 Oikawa et al published the most often referenced modification. 21 They reported cosmetically satisfactory outcomes in 100 patients, which were obtained by avoiding the use of electrocautery and dissecting the temporal muscle in a retrograde fashion.…”
Section: Aesthetic Resultsmentioning
confidence: 99%
“…15 In our work, this device was not included as a variable that could influence the results. Park and Hamm quantified temporal hollowing by measuring the thickness of the muscle, but again this approach reflects only a single 2D measure and may be disposed to error based on the temporal muscle reattachment.…”
Section: Radiological Atrophy Measurementsmentioning
confidence: 99%
“…Postoperatively, the deformity was no longer present, and the scalp was symmetric, bilaterally. The use of Alloderm™ implants in the frontotemporal region during cranioplasty may provide a buffer given that this area is particularly susceptible to thinner skin and muscle atrophy, as was present in our patient [8]. Additionally, given that defects in this region can lead to significant disfigurement, Alloderm™ may be used to enhance postoperative cosmetic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2 The most common complication of temporalis muscle is atrophy and also various studies have shown the atrophy of muscle after craniofacial surgeries with extensive dissection or electrocautery of the muscle causing cosmetic deformity. 3,4 However, we routinely use electrocautery while dissecting the temporalis muscle from the calvarium to minimize bleeding.…”
Section: Discussionmentioning
confidence: 99%